Mid-term subclinical myocardial injury detection in patients who recovered from COVID-19 according to pulmonary lesion severity - Chamtouri, Ikram; Kaddoussi, Rania; Abroug, Hela; Abdelaaly, Mabrouk; Lassoued, Taha; Fahem, Nesrine; Cheikh'Hmad, Saoussen; Ben Abdallah, Asma; Jomaa, Walid; Ben Hamda, Khaldoun; Maatouk, Faouzi (Frontiers in Cardiovascular Medicine, 2022)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) may cause damage to the cardiovascular system during the acute phase of the infection. However, recent studies reported mid- to long-term subtle cardiac injuries after recovering from acute coronavirus disease 2019 (COVID-19). This study aimed to determine the relationship between the severity of chest computed tomography (CT) lesions and the persistence of subtle myocardial injuries at mid-term follow-up of patients who recovered from COVID-19 infection. Methods All patients with COVID-19 were enrolled prospectively in this study. Sensitive troponin T (hsTnT) and chest CT scans were performed on all patients during the acute phase of COVID-19 infection. At the mid-term follow-up, conventional transthoracic echocardiograph and global longitudinal strain (GLS) of the left and right ventricles (LV and RV) were determined and compared between patients with chest CT scan lesions of < 50% (Group 1) and those with severe chest CT scan lesions of greater or equal to 50% (Group 2). Results The mean age was 55 ± 14 years. Both LV GLS and RV GLS values were significantly decreased in group 2 (p = 0.013 and p = 0.011, respectively). LV GLS value of more than −18 was noted in 43% of all the patients, and an RV GLS value of more than −20 was observed in 48% of them. The group with severe chest CT scan lesions included more patients with reduced LV GLS and reduced RV GLS than the group with mild chest CT scan lesions [(G1:29 vs. G2:57%, p = 0.002) and (G1:36 vs. G2:60 %, p = 0.009), respectively]. Conclusion Patients with severe chest CT scan lesions are more likely to develop subclinical myocardial damage. Transthoracic echocardiography (TTE) could be recommended in patients recovering from COVID-19 to detect subtle LV and RV lesions.